Cover Image, Volume 22, Issue 11. Issue 11 (19th October 2020) - Haws, Robert; Brady, Sheila; Davis, Elisabeth; Fletty, Kristina; Yuan, Guojun; Gordon, Gregory; Stewart, Murray; Yanovski, Jack
Abstract : The outside front cover image is based on the Original Article Effect of Setmelanotide, an MC4R Agonist, on Obesity in Bardet‐Biedl Syndrome by Robert Haws et al., https://doi.org/10.1111/dom.14133 .